Understanding the Perceived Threat of the Risk of Graft Rejections - Anna Forsberg; Annette Lennerling; Isabell Fridh; Veronika Karlsson; Madeleine Nilsson (SAGE Publishing, 2015)
From a clinical viewpoint, graft rejection is one of the greatest threats faced by an organ transplant recipient (OTR). We propose a middle-range theory (MRT) of Perceived Threat of the Risk of Graft Rejection (PTRGR) as a contribution to the practice of transplant nursing. It could also apply to the detection of risky protective behavior, that is, isolation, avoidance, or non-adherence. The proposed MRT covers the following concepts and the relationship between them: transplant care needs, threat reducing interventions, intervening variables, level of PTRGR, protective strategies, and evidence-based practice. Parts of this theory have been empirically tested and support the suggested relationship between some of the concepts. Further tests are needed to strengthen the theoretical links. The conceptual framework might serve as a guide for transplant nurses in their efforts to promote post-transplant health and reduce threat-induced emotions.